ACCESSIBILITY OF EDUCATION THROUGH OPEN HIGH SCHOOL: A LITERATURE REVIEW FROM PIERRE BOURDIEU'S PERSPECTIVE: AKSESIBILITAS PENDIDIKAN MELALUI SMA TERBUKA: TINJAUAN LITERATUR DARI PERSPEKTIF PIERRE BOURDIEU - Vevy Julianty; Kendedes Tambunan; Saliman; Riko Septiantoko (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study analyzes the accessibility of secondary education through the Open High School (SMA Terbuka) program as an alternative solution for communities in remote areas facing geographical and economic constraints. Using Pierre Bourdieu's theoretical framework, the study explores the dynamics of capital (economic, cultural, social, and symbolic), habitus , and the educational field in line with the context of Open High School implementation. The research methodology adopts a desk study approach with qualitative analysis of policy data and relevant literature. The findings indicate that Open High Schools significantly increase the availability of educational services, but still face challenges in terms of digital accessibility and student participation. Disparities in technological literacy and digital infrastructure are undoubtedly major obstacles to the program's effectiveness. Bourdieusian analysis reveals how inequality in students' initial capital affects their ability to utilize alternative educational opportunities. The study concludes that Open High Schools have great potential in reducing educational inequality, but requires comprehensive policy intervention to address structural barriers. The research recommendations emphasize the importance of strengthening digital infrastructure, increasing technological literacy, and empowering communities to maximize the benefits of Open High Schools as an instrument for realizing equitable and just education.